Prioritization of the Forest Species Most Exploited by the Communities Bordering the Natural Forests of Pob`e and Dogo-K´etou in Southeastern Benin, West Africa: An Ethnobotanical Approach - GANGLO, COSSI JEAN; KINGBO, Armand; KOURA, Kourouma (My University, 2023)
Benin is not a big forest country, and the sustainable management of forest relics and their resources is a priority for the managers. This study was conducted in the forest regions of Pobè and Kétou located in Southeast Benin with the objective of characterizing the ethnobotanical forest species prioritized by the local populations for their different uses. Specifically, it aimed to identify the ethnobotanical priority species for conservation, characterize the ethnobotanical value of these priority species, and analyze the tree organ harvesting methods used for the sustainable management of the forest species. Data have been collected from 287 local populations investigated and on the specimens collected on the field, which allowed to identify the scientific name. The combination of the citation frequencies, the method of reproduction, the vulnerability scores, and the IUCN status of the species has allowed to identify five priority ethnobotanical species per forest. The software Ri386_3.5.1 has been used for the different analysis such as the calculation of the various frequencies and the correspondence factor analysis to show the relationships between socioethnic groups, organs used, and the categories of use. The priority species identified in the forest of Pobè are Milicia excelsa, Khaya senegalensis, Anogeissus leiocarpa, Ceiba pentandra, and Adansonia digitata. The priority species identified in the forest of Dogo-Kétou are Vitellaria paradoxa, Prosopis africana, Pterocarpus erinaceus, Khaya senegalensis, and Anogeissus leiocarpa. This study has revealed 54 tree species gathered into 47 genera and 25 botanical families. Their different parts have been harvested for many kinds of utilization such as medicinal, commercial, feeding, medico-magic, and artisanal. The most commonly used organs were leaves, fruits, seeds, barks, roots, and wood. The harvesting methods include cutting poles, cutting twigs and branches to harvest leaves, debarking the trunk, felling trees for wood, cutting roots, picking and harvesting fruits and seeds, and harvesting of flowers. Cutting down trees and picking flowers, fruits, and seeds have been the methods of harvesting, which affect negatively regeneration of the tree populations. It is then important to sensitize the local people on the sustainable management of their forest resources through the conception and implementation of a project program focused on forest conservation.
Keywords: Priority species; ethnobotanical value; harvesting methods; Kétou-Dogo; Pobè; Benin